THE IMPORTANCE OF TEACHING THE DISCIPLINE OF EDUCATION IN THE PERSONAL DEVELOPMENT OF STUDENTS - Makulov Shukhrat Kholmatjonovich (The Conference Hub, 2025)
This article analyzes the importance of teaching the discipline of education in the personal development of students. The article focuses on the fact that the science of education plays an important role not only in teaching moral and social values, but also in shaping the personality of students, understanding social responsibility and supporting personal development. The article also shows how interactive methods, such as the "role play" method, can be used in teaching the discipline of parenting. This method helps students develop personal and social skills by making them work in a team and feel socially responsible. The article analyzes in detail the importance of the discipline of education in the personal and professional development of students, as well as the use of interactive methods in the educational process.
Keywords: Educational Science, personal development, interactive methods, role-playing, social responsibility, creative thinking, moral values, teamwork, educational technologies, methodological approaches, student personality, personal and professional growth, pedagogical methods.